Women's economic empowerment strategy - First foundation-wide strategy for gender equality - Wilde, Vicky (Bill & Melinda Gates Foundation, 2017)
Presented by Vicky Wilde (BMGF), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017, where the Platform is hosted (by KIT Royal Tropical Institute)